2021
DOI: 10.1016/j.jns.2021.117462
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness and impact of COVID 19 infection at tertiary care neurology centers in Pakistan

Abstract: Objective We aimed to assess the response and impact of response to pandemic at tertiary care centers in Pakistan especially pertaining to neurological care, facilities and training. Methods A pre-tested survey form was sent to 40 neurology tertiary care centers in all the provinces in the country in the first week of July 2020. 33 filled forms were received, out of which 18 were public (government) and 15 were private hospitals. Results Esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Of the 95,460 studies identified through database searching, 95,418 records were excluded because the abstract or the title did not fulfil the inclusion criteria for this review (i.e., were not studies about neurology residents’/trainees’ perspectives on the impact of COVID-19 on their residency or quantitative analysis of these findings). Forty-two full papers were assessed for eligibility, and, eventually, only 12 studies met the aforementioned full criteria and underwent data extraction ( Figure 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Information related to year of publication, study design, sample size, study population, time and country of assessment is reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 95,460 studies identified through database searching, 95,418 records were excluded because the abstract or the title did not fulfil the inclusion criteria for this review (i.e., were not studies about neurology residents’/trainees’ perspectives on the impact of COVID-19 on their residency or quantitative analysis of these findings). Forty-two full papers were assessed for eligibility, and, eventually, only 12 studies met the aforementioned full criteria and underwent data extraction ( Figure 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Information related to year of publication, study design, sample size, study population, time and country of assessment is reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Encouragingly, 21% of those surveyed reported no reduction (0–20%) in supervision at work during the pandemic [ 23 ]. In a study evaluating the impact of COVID-19 in tertiary care neurology centers in Pakistan, it was found that 69.7% of neurology trainees were assigned to work in COVID-19 isolation units, and 66.7% of residents/interns had their daily duty schedules converted to on-call schedules only [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-center study was conducted in Pakistan evaluating preparedness and the impact of COVID-19 of the neurological / stroke care and training of residents and fellows [ 45 ]. Both societies organized many public awareness and media awareness activities related to COVID-19 neurological manifestations and stroke care in COVID-19 patients.…”
Section: Objectives and Methodsmentioning
confidence: 99%
“…An unexpected halting effect of these programs was due to the fear of contracting the COVID-19 infection. Simultaneously there was a significant decline in emergency presentations of patients with potentially serious diseases (for example, acute coronary syndrome and stroke) [ [45] , [46] , [47] ]. While there is no clear evidence that this decrease in hospital admissions of patients with acute vascular syndromes may have resulted in serious effects, the realization that patients may not come to the hospital requires active public efforts to promote the safety of care in such situations.…”
Section: Objectives and Methodsmentioning
confidence: 99%